Segmental cherry angiomas with microtia and hepatomegaly: A case report - Niral K Sheth; Mohabat D Baria; Nilam K Damor; Rahul S Bhabhor (Wolters Kluwer Medknow Publications, 2020)
Cherry angioma or Campbell de Morgan spots or senile hemangioma is an acquired, well-circumscribed vascular lesion, occurring in adulthood and increasing in number with age. We report the case of a 60-year-old male patient with segmental cherry angioma, hepatomegaly, and ear abnormality.